Contrasting concepts within the US and across the African diaspora: motherhood status reconsidered comparatively. (2nd April 2016) - Simien, Evelyn M.
Abstract : This essay provides another perspective on motherhood status, involving an often ignored aspect of race and gender relations in U.S politics. It offers a slight caveat to Tripp's account. Whereas motherhood status serves a legitimizing force and allows women to enter the public domain with relative ease in African societies, it can work more to a woman's disadvantage and make her less likely to enter the public domain in the U.S. Herein lies the contribution of this essay. The author recognizes that prevailing notions of motherhood in the African context do not correspond well with traditional Western views of this same axis of identity especially for U.S. politics. She observes that motherhood has real conceptual meaning and comparatively so for women within the U.S. and across the African diaspora. The meaning of motherhood essentially travels and goes from passive attribute to elevated resource in one context versus the other. It has currency as an external thing, a deployable resource or reputational asset that when applied to the case of African societies becomes the basis for understanding the ways in which the quest for "equality" over "difference" became synonymous with an end goal of the civil rights movement.